A current review of local metronidazole antibiotics for the treatment of periodontal disease - Mohd Zavi, Nora Azirah; Mohamed Halim, Muhammad Lutfi; Mohamad, Mohd Yusof (IIUM Press, 2023)
Periodontal disease affects around 14.5% of the global adult population. It affects the tooth's supporting tissues, causing inflammation and tooth loss. Periodontitis treatment aims to prevent further disease progression by restoring the lost tissue and preventing bacterial infection. Nevertheless, periodontal breakdown may still occur post-treatment due to the periodontal pathogens. Antibiotics were utilized to control and prevent the infection. Local drug delivery system (LDD) is being developed to deliver the antibiotic due to its site-specific benefits. Metronidazole (MET) is widely used to treat periodontal nfection following treatments due to its efficacy against obligate anaerobes and broad-spectrum characteristics. Despite its advantages, MET is attributed to systemic side effects. Therefore, this article aimed to review in vitro, in vivo, and clinical studies on the current local application of MET to treat periodontal diseases. 13 relevant research articles were analysed and provide valuable insights into the local application of metronidazole for periodontal treatment.